A newly discovered Gigantidas bivalve mussel from the Onnuri Vent Field in the northern Central Indian Ridge. (July 2020) - Jang, Sook-Jin; Ho, Phuong-Thao; Jun, Si-Yeong; Kim, Dongsung; Won, Yong-Jin
Abstract: We describe a new vent mussel species, Gigantidas vrijenhoeki n. sp., from material collected at a depth of 2022 m in the newly discovered Onnuri Vent Field (OVF) during the 2018 expedition to the Central Indian Ridge. This large modioliform mussel thrives around diffusive vents in aggregation with another dominant hydrothermal vent mussel, Bathymodiolus marisindicus . G. vrijenhoeki n. sp. was distinguished from its neighboring B. marisindicus by its distinct shell profile, which consists of an elongated shell with a short and low anterior region, high expanded posterior region, and deep ventral concavity. Visually, the new mussel species resembles G . securiformis ; however, it is clearly distinguished by several shell and anatomical features. Genetically, the new species is closely related to two undescribed Gigantidas species found in the cold seeps of the western Pacific. Phylogenetic analysis of G. vrijenhoeki n. sp. supports the connectivity of vent fauna between the Indian Ocean and the western Pacific in the past. To the best of our knowledge, this is the first record of a Gigantidas species in the Indian Ocean. In addition, we found gill-associated sulfur-oxidizing and methane-oxidizing bacteria, Gammaproteobacteria and Epsilonproteobacteria, symbionts present on this new species. Their composition was clearly different from symbionts found on the co-occurring B. marisindicus at the OVF. Notably, the sulfurovum -related Epsilonproteobacteria on the G. vrijenhoeki n. sp. were phylogenetically distinct from the family of Bathymodiolinae-related Epsilonproteobacteria . Taken together, the co-occurrence of two mussel species at the new vent field and their distinct gill symbiotic communities provides a useful setting in which to study the genetic connectivity of vent mussels along the Central Indian Ridge and the evolutionary dynamics between host mussels and symbionts. Highlights: A new deep-sea Bathymodiolinae mussel species of the genus Gigantidas was described. This is the first record of Gigantidas species in the Indian Ocean. This new species was clustered phylogenetically with seep mussel species of the western Pacific. Sulfur- and methane-oxidizing symbiotic bacteria were detected from the gill of this new species.